Adhesive Capsulitis of the Ankle (Frozen Ankle): An Infrequent Syndrome - Daniel Aguilar-Núñez; Dina Hamed-Hamed; María Aguilar-García; María Cuevas-Cervera; José Javier Pérez-Montilla; Ana González-Muñoz; Leo Pruimboom; Santiago Navarro-Ledesma (Biomedicines, 2023)
Adhesive capsulitis, characterized by progressive fibrosis, causes a gradual, painful loss of both active and passive articular motion, leading to the final contracture of the joint capsule. The condition commonly referred to as “frozen ankle” (FA), which Goldman was the first to use, relates to the ankle joint and is challenging to both diagnose and treat. Data acquired from people who suffer from this type of damage in other joints such as the shoulder, hip, and wrist also exists. Despite the fact that a well-defined model for the medical management of FA does not exist, a wide spectrum of local treatments, both surgical and non-surgical, exist. This review gives an overview of the current scientific position of the frozen ankle in terms of evolutionary factors, etiology, the different mechanisms of action involved, current treatment options, and other possible interventions based on recent discoveries of pathophysiological mechanisms. The application of extracorporeal shockwave therapy, stretching exercises, and corticosteroid injections combined with physical therapy modalities that enhance pain management, range of motion, and functional capacity is highly advisable for the treatment of adhesive capsulitis, commonly known as “frozen joints”. Furthermore, the addition of interventions both impacting and analyzing chronic hypoxia, low-grade inflammation, and sedentary life is proposed.